Design of novel running leggings with thermoplastic polyurethane membrane compression zones. Issue 8 (April 2019) - Goncu Berk, Gozde; Kahveci, Sinem
Compression garments are widely used by athletes to improve athletic performance and to avoid potential injuries. Some compression garments are developed to exert pressure on muscle groups via thermoplastic polyurethane (TPU) membrane layers laminated on the textile surface. This study investigates the effect of novel TPU membrane patterns on muscle performance of the lower extremities and on the comfort parameters of air and water vapor permeability. Three novel running leggings with TPU membrane compression zones were designed to exert pressure on the major muscle groups used during running. Electromyography (EMG) measurements of the female participants wearing the designed leggings with TPU membranes, conventional leggings and shorts were recorded during a standardized squat protocol via a wireless surface EMG system. A repeated measures analysis of variance with a Greenhouse–Geisser correction determined that the mean root of mean square values for the EMG signals retrieved from the rectus femoris, vastus lateralis, gastrocnemius and hamstring muscles while wearing a specific legging design revealed statistically significant reductions in muscle activation. On the other hand, comfort tests exhibited low water vapor permeability and air permeability results when the textile surface was laminated with the TPU membrane. TPU membranes laminated on athletic wear to create compression zones could be effective in reducing muscle activation. Comfort performance is another essential design parameter that should be integrated into the design decisions. Large surfaces of solid TPU membranes should be minimized and surface textures should be employed for increased breathability.